Hubungan Literasi Digital dengan Kecemasan Orang Tua Terhadap Aktivitas Bermain Game Online Anak di SD Plus Al-Ghifari Kota Bandung - Dilla Indah Sari; Mamat Lukman; Nenden Nur Asriyani Maryam (Universitas Malahayati Lampung, 2026)
ABSTRACT The rapid development of digital technology has made online gaming a popular activity among elementary school children, which often triggers anxiety in parents regarding the negative impacts on child development. Parental digital literacy is hypothesized to play a role in shaping psychological responses to these challenges. The purpose of this study was to determine the relationship between digital literacy and parental anxiety levels regarding children's online gaming activities at SD Plus Al-Ghifari, Bandung. A quantitative correlational study with a cross-sectional approach was conducted in March 2026. A total of 84 parents of 4th and 5th-grade students were recruited using purposive sampling. Data were collected using the Digital Literacy Scale (25 items, Cronbach's alpha 0.950) and the State-Trait Anxiety Inventory Form Y-2 (STAI-T) Indonesian version (20 items, Cronbach's alpha 0.91), then analyzed using univariat (frequency distribution) and bivariate (Spearman's rank correlation) analyses. The results showed that 76 respondents (90,5%) had high digital literacy, while 38 respondents (45.2%,) had moderate anxiety and 28 respondents (33,3%) had severe anxiety. Spearman's correlation test showed a significant negative relationship between digital literacy and parental anxiety (ρ = -0.460, p = 0.000). This study concludes that higher digital literacy is associated with lower anxiety levels. However, high digital literacy does not automatically guarantee low anxiety, as cognitive and ethical dimensions as well as trait anxiety also play a role. It is recommended that community nurses develop holistic digital literacy interventions and facilitate support groups for parents. Keywords: Digital Literacy, Parental Anxiety, Online Gaming, Elementary School Children, Digital Parenting. ABSTRAK Kemajuan teknologi telah meningkatkan paparan game online pada anak usia sekolah dasar, sehingga orang tua perlu literasi digital yang memadai karena keterbatasan literasi digital dapat menyulitkan pengawasan dan memicu kecemasan orang tua. Penelitian ini bertujuan menganalisis hubungan antara literasi digital dan kecemasan orang tua terhadap aktivitas bermain game online anak di SD Plus Al Ghifari. Penelitian ini menggunakan desain kuantitatif korelasional dengan pendekatan cross-sectional pada Maret 2026. Sebanyak 84 orang tua siswa kelas 4 dan 5 direkrut menggunakan teknik purposive sampling. Data dikumpulkan menggunakan Skala Literasi Digital dan STAI-T versi Indonesia, kemudian dianalisis secara univariat (distribusi frekuensi) dan bivariat (korelasi Spearman). Hasil penelitian menunjukkan 76 responden (90,5%) memiliki literasi digital tinggi, sedangkan 38 responden (45,2%) mengalami kecemasan sedang dan 28 responden (33,3%) mengalami kecemasan berat. Uji korelasi Spearman menunjukkan hubungan negatif yang signifikan antara literasi digital dan kecemasan orang tua (ρ = -0,460, p = 0,000). Penelitian ini menyimpulkan bahwa semakin tinggi literasi digital, semakin rendah kecemasan yang dialami. Namun, literasi digital yang tinggi tidak secara otomatis menjamin kecemasan rendah karena dimensi kognitif, etika, dan trait anxiety turut berperan. Disarankan bagi perawat komunitas untuk mengembangkan intervensi peningkatan literasi digital secara holistik dan memfasilitasi kelompok dukungan bagi orang tua. Kata Kunci: Literasi Digital, Kecemasan Orang Tua, Game Online, Anak Usia Sekolah Dasar, Pengasuhan Digital.